2013
DOI: 10.1002/jgrd.50220
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal ozone variations in the stratosphere revealed in observations from the Superconducting Submillimeter‐Wave Limb‐Emission Sounder (SMILES) on board the International Space Station (ISS)

Abstract: [1] Considerable uncertainties remain in the global pattern of diurnal variation in stratospheric ozone, particularly lower to middle stratospheric ozone, which is the principal contributor to total column ozone. The Superconducting Submillimeter-Wave LimbEmission Sounder (SMILES) attached to the Japanese Experiment Module (JEM) on board the International Space Station (ISS) was developed to gather high-quality global measurements of stratospheric ozone at various local times, with the aid of superconducting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
95
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 32 publications
11
95
1
Order By: Relevance
“…2 the strength of D O 3 differs for March, June, September and December, which indicates a seasonal variation in the daily ozone cycle. The existence of a seasonal variation of the daily ozone cycle was also suggested by Sakazaki et al (2013). We discuss the seasonal effects in more detail in Sect.…”
Section: The Daily Ozone Cyclementioning
confidence: 60%
See 3 more Smart Citations
“…2 the strength of D O 3 differs for March, June, September and December, which indicates a seasonal variation in the daily ozone cycle. The existence of a seasonal variation of the daily ozone cycle was also suggested by Sakazaki et al (2013). We discuss the seasonal effects in more detail in Sect.…”
Section: The Daily Ozone Cyclementioning
confidence: 60%
“…Satellite-based observations from SMILES (Kikuchi et al, 2013), SABER and MLS showed a morning minimum and a late-afternoon maximum in the daily ozone cycle in the tropics and subtropics (Huang et al, 2008;Sakazaki et al, 2013). In Fig.…”
Section: The Daily Ozone Cyclementioning
confidence: 88%
See 2 more Smart Citations
“…Recently, Sakazaki et al (2013a; hereafter S13) revealed diurnal variations in ozone concentration from the lower to upper stratosphere using data from both the Superconducting Submillimeter-Wave Limb-Emission Sounder (SMILES) and chemical transport models (CTMs). They showed that the peak-to-peak difference in ozone levels reaches 8 % during a day.…”
Section: T Sakazaki Et Al: Sunset-sunrise Difference In Solar Occulmentioning
confidence: 99%